Long‐term effects of ciclosporin and oclacitinib on mediators of tolerance, regulatory T‐cells, IL‐10 and TGF‐β, in dogs with atopic dermatitis. Issue 2 (8th December 2022) - Herrmann, Ina; Mamo, Lisa B.; Holmes, Jenny; Mohammed, Javid P.; Murphy, K. Marcia; Bizikova, Petra
Abstract: Background: Atopic dogs often are managed with allergen‐specific immunotherapy (AIT) and concurrent dosages of ciclosporin (CSA) or oclacitinib to alleviate their clinical signs. Both drugs might affect proper tolerance induction by inhibiting regulatory T‐cell (Treg) induction. Hypothesis/Objectives: We evaluated Treg cell numbers and serum interleukin (IL)‐10 and transforming growth factor‐beta (TGF‐β)1 levels in dogs diagnosed with atopic dermatitis (AD) and successfully treated with either CSA or oclacitinib for nine or more months. Animals: We included 15 dogs receiving oclacitinib, 14 dogs treated with CSA, 15 healthy dogs, 13 dogs with untreated moderate‐to‐severe AD and 15 atopic dogs controlled with AIT. Materials and Methods: Peripheral blood CD4+CD25+FOXP3+ T‐cell percentages were determined using flow cytometry. Serum concentrations of IL‐10 and TGF‐β1 were measured by enzyme‐linked immunosorbent assay. Results: The percentage of Treg cells in the CSA group was significantly lower in comparison with the healthy group ( p = 0.0003), the nontreated AD group ( p = 0.0056) or the AIT group ( p = 0.0186). There was no significant difference in Treg cell percentages between the CSA and oclacitinib groups, nor between the oclacitinib and the healthy, nontreated AD or AIT‐treated dogs. No significant differences were detected in IL‐10 and TGF‐β1 serum concentrations between the five groups. Conclusions and Clinical Relevance: Lower Treg cell percentages in the CSA‐treated dogs suggest an impact of this drug on this cell population; however, it does not necessarily mean that it diminishes tolerance. Functionality and cytokine production may be more important than the number of Treg cells. Further studies evaluating the treatment outcome of dogs receiving AIT and concurrent drugs are needed to show clinical relevance. Abstract : Background – Atopic dogs often are managed with allergen‐specific immunotherapy (AIT) and concurrent dosages of ciclosporin (CSA) or oclacitinib to alleviate their clinical signs. Both drugs might affect proper tolerance induction by inhibiting regulatory T‐cell (Treg) induction. Hypothesis/Objectives – We evaluated Treg cell numbers and serum interleukin (IL)‐10 and transforming growth factor‐beta (TGF‐β)1 levels in dogs diagnosed with atopic dermatitis (AD) and successfully treated with either CSA or oclacitinib for nine or more months. Conclusions and Clinical Relevance – Lower Treg cell percentages in the ciclopsorin‐treated dogs suggest an impact of this drug on this cell population; however, it does not necessarily mean that it diminishes tolerance. Functionality and cytokine production may be more important than the numbers of Treg cells. Further studies evaluating the treatment outcome of dogs receiving AIT and concurrent drugs are needed to show clinical relevance. Résumé: Contexte: Les chiens atopiques sont souvent traités avec une immunothérapie spécifique d'allergène (AIT) et des doses concomitantes de ciclosporine ou d'oclacitinib pour atténuer leurs signes cliniques. Les deux médicaments pourraient affecter l'induction de la tolérance appropriée en inhibant l'induction des lymphocytes T régulateurs (Treg). Hypothèse/Objectifs: Nous avons évalué le nombre de cellules Treg et les taux sériques d'interleukine (IL)‐10 et de TGF‐β‐1 chez des chiens diagnostiqués avec une dermatite atopique (DA) et traités avec succès par la ciclosporine ou l'oclacitinib pendant neuf mois ou plus. Animaux: Nous avons inclus 15 chiens recevant de l'oclacitinib, 14 chiens traités par ciclosporine, 15 chiens sains, 13 chiens atteints de DA modérée à sévère non traitée et 15 chiens atopiques contrôlés par AIT. Matériels et méthodes: Les pourcentages de lymphocytes T CD4+CD25+FOXP3+ du sang périphérique ont été déterminés par cytométrie de flux. Les concentrations sériques d'IL‐10 et de TGF‐β1 ont été mesurées par dosage immuno‐enzymatique. Résultats: Le pourcentage de cellules Treg dans le groupe ciclosporine était significativement plus faible par rapport au groupe sain ( p = 0, 0003 ), au groupe AD non traité ( p = 0, 0056 ) ou au groupe AIT ( p = 0, 0186 ). Il n'y avait pas de différence significative dans les pourcentages de cellules Treg entre le groupe ciclosporine et oclacitinib, ni entre l'oclacitinib et les chiens sains non traités AD ou traités AIT. Aucune différence significative n'a été détectée dans les concentrations sériques d'IL‐10 et de TGF‐β1 entre les cinq groupes. Conclusions et pertinence clinique: Des pourcentages de cellules Treg plus faibles chez les chiens traités à la ciclosporine suggèrent un impact de ce médicament sur cette population cellulaire ; cependant, cela ne signifie pas nécessairement qu'il diminue la tolérance. La fonctionnalité et la production de cytokines peuvent être plus importantes que le nombre de cellules Treg. D'autres études évaluant les résultats du traitement des chiens recevant l'AIT et des médicaments concomitants sont nécessaires pour montrer la pertinence clinique. Resumen: Introducción: los perros atópicos a menudo se tratan con inmunoterapia específica para alérgenos (AIT) y dosis simultáneas de ciclosporina u oclacitinib para aliviar sus signos clínicos. Ambos fármacos podrían afectar la inducción de tolerancia adecuada al inhibir la inducción de células T reguladoras (Treg). Hipótesis/Objetivos: Evaluamos el número de células Treg y los niveles séricos de interleuquina (IL)‐10 y factor de crecimiento transformante‐beta (TGF‐β)1 en perros diagnosticados con dermatitis atópica (AD) y tratados con éxito con ciclosporina u oclacitinib durante nueve o mas meses Animales: Incluimos 15 perros que recibieron oclacitinib, 14 perros tratados con ciclosporina, 15 perros sanos, 13 perros con AD de moderada a grave no tratada y 15 perros atópicos controlados con AIT. Materiales y métodos: Los porcentajes de células T CD4+CD25+FOXP3+ en sangre periférica se determinaron mediante citometría de flujo. Las concentraciones séricas de IL‐10 y TGF‐β1 se midieron mediante ensayo inmunoabsorbente ligado a enzimas. Resultados: El porcentaje de células Treg en el grupo de ciclosporina fue significativamente menor en comparación con el grupo sano ( p = 0, 0003), el grupo AD no tratado ( p = 0, 0056) o el grupo AIT ( p = 0, 0186). No hubo diferencias significativas en los porcentajes de células Treg entre el grupo de ciclosporina y oclacitinib, ni entre el oclacitinib y los perros sanos, no tratados con AD o tratados con AIT. No se detectaron diferencias significativas en las concentraciones séricas de IL‐10 y TGF‐β1 entre los cinco grupos. Conclusiones y relevancia clínica: Los porcentajes más bajos de células Treg en los perros tratados con ciclosporina sugieren un impacto de este fármaco en esta población celular; sin embargo, no significa necesariamente que disminuya la tolerancia. La funcionalidad y la producción de citoquinas pueden ser más importantes que el número de células Treg. Se necesitan más estudios que evalúen el resultado del tratamiento de perros que reciben AIT y medicamentos concurrentes para mostrar relevancia clínica. Zusammenfassung: Hintergrund: Atopische Hunde werden oft mit Allergen‐spezifischer Immuntherapie (AIT) gemanagt, wobei gleichzeitig Ciclosporin oder Oclacitinib verabreicht werden, um ihre klinischen Zeichen zu lindern. Beide Medikamente können die Toleranzinduktion durch eine Inhibition der regulatorischen T Zellen (Treg) Induktion beeinflussen. Hypothese/Ziele: Wir evaluierten die Treg Zellzahlen und Serum Interleukin (IL)‐10 und Transforming Growth Factor‐beta (TGF‐β) Werte bei Hunden, die mit einer atopischen Dermatitis (AD) diagnostiziert worden waren und entweder mit Ciclosporin oder mit Oclacitinib für neun Monate oder länger erfolgreich behandelt worden waren. Tiere: Wir inkludierten 15 Hunde, die Oclacitinib erhielten, 14 Hunde, die mit Ciclosporin behandelt worden waren, 15 gesunde Hunde, 13 Hunde mit unbehandelter moderater‐bis‐hochgradiger AD und 15 atopische Hunde, die mit AIT kontrolliert waren. Materialien und Methoden: Periphere Blut CD4+CD25+FOXP3+ T‐Zell Prozentanteile wurden mittels Flowzytometrie bestimmt. Serumkonzentrationen von IL‐10 und TGF‐β wurden mittels Enzym‐linked Immunosorbent Assay gemessen. Ergebnisse: Der Prozentanteil der Treg Zellen in der Ciclosporingruppe war signifikant niedriger im Vergleich zur gesunden Gruppe ( p = 0, 0003), zur nichtbehandelten AD‐Gruppe ( p = 0, 0056), oder der AIT‐Gruppe ( p = 0, 0186). Es bestand kein signifikanter Unterschied zwischen den prozentualen Anteilen der Treg Zellen zwischen Ciclosporin und der Oclacitinib Gruppe, und auch nicht zwischen der Oclacitinib und der gesunden, nichtbehandelten AD‐Gruppe, oder den AIT‐behandelten Hunden. Es wurden keine signifikanten Unterschiede zwischen IL‐10 und TGF‐β1 Serumkonzentrationen zwischen den fünf Gruppen gefunden. Schlussfolgerungen und klinische Bedeutung: Niedrigere Prozentanteile der Treg Zellen bei den Ciclosporin‐behandelten Hunden weisen darauf hin, dass dieses Medikament auf diese Zellpopulation einen Einfluss hat; es bedeutet jedoch nicht unbedingt, dass es die Toleranz vermindert. Die Funktionalität und die Ciclosporin Produktion könnte wichtiger sein als die Anzahl der Treg Zellen. Weitere Studien sind nötig, die den Behandlungserfolg bei Hunden, die AIT und gleichzeitig Medikamente erhalten, evaluieren, um die klinische Relevanz zu zeigen. 要約: 背景: アトピー犬は、しばしばアレルゲン特異的免疫療法(AIT)を行い、同時にシクロスポリンやオクラシチニブを投与して臨床症状を軽減している。両薬剤は、制御性T細胞(Treg)の誘導を阻害することにより、適切な寛容誘導に影響を与える可能性がある。 仮説/目的: 本研究の目的は、 アトピー性皮膚炎(AD)と診断され、シクロスポリンまたはオクラシチニブによる9ヶ月以上の治療に成功した犬において、Treg細胞数、血清インターロイキン(IL)‐10およびトランスフォーミング増殖因子‐β(TGF‐β)1レベルを評価することであった。 供試動物: オクラシチニブ投与犬15頭、シクロスポリン投与犬14頭、健常犬15頭、未治療の中等度から重度のAD犬13頭、AITでコントロールしたアトピー犬15頭を対象とした。 材料と方法: 末梢血CD4+CD25+FOXP3+ T細胞の割合をフローサイトメトリーで測定した。血清中のIL‐10およびTGF‐β1濃度は、酵素結合免疫吸着法で測定した。 結果: シクロスポリン投与群では、健常群(p=0.0003)、AD未治療群(p=0.0056)、AIT群(p=0.0186)と比較して、Treg細胞の割合が有意に低下した。シクロスポリン群とオクラシチニブ群、オクラシチニブ群と健常群、AD未治療群、AIT治療群との間でもTreg細胞の割合に有意差はなかった。IL‐10およびTGF‐β1血清濃度には5群間で有意差は検出されなかった。 結論と臨床的関連性: シクロスポリン投与犬におけるTreg細胞の割合の低下は、シクロスポリンがこの細胞集団に影響を与えることを示唆していた。しかし、それは必ずしも耐性を低下させることを意味するものではない。機能性やサイトカイン産生は、Treg細胞数よりも重要である可能性がある。臨床的な関連性を示すためには、AITと併用薬を投与された犬の治療成績を評価する更なる研究が必要である。 摘要: 背景: 特应性犬通常通过过敏原特异性免疫治疗 (AIT) 和同时给予环孢素或奥拉替尼缓解其临床症状。两种药物均可能通过抑制调节性 T 细胞 (Treg) 诱导影响适当的耐受诱导。 假设/目的: 我们在诊断为特应性皮炎 (AD) 并成功接受环孢素或奥拉替尼治疗9个月或以上的犬中评价了 Treg 细胞数量以及血清白细胞介素 (IL)‐10 和转化生长因子‐β (TGF‐β)1水平。 动物: 我们纳入了15只接受奥拉替尼的犬、14只接受环孢素治疗的犬、15只健康犬、13只未治疗的中度至重度 AD 犬和15只接受 AIT 控制的特应性犬。 材料和方法: 使用流式细胞术测定外周血CD4 + CD25 + FOXP3 + T细胞百分比。采用酶联免疫吸附法检测血清 IL‐10 和TGF‐β1的浓度。 结果: 环孢素组的 Treg 细胞百分比显著低于健康组 (p = 0.0003)、未治疗 AD 组 (p = 0.0056) 或 AIT 组 (p = 0.0186)。环孢素和奥拉替尼组、奥拉替尼和健康、未治疗 AD 或 AIT 治疗犬之间的 Treg 细胞百分比无显著差异。5组间 IL‐10 和TGF‐β1血清浓度未检测到明显差异。 结论和临床相关性: 环孢素给药犬中较低的 Treg 细胞百分比表明该药物对该细胞群有影响；然而，这并不一定意味着其会降低耐受性。功能和细胞因子的产生可能比 Treg 细胞的数量更重要。需要进一步研究评价接受 AIT 和伴随药物的犬的治疗结果，以显示临床相关性。 Resumo: Contexto: Cães atópicos geralmente são tratados com imunoterapia alérgeno‐específica (AIT) e dosagens concomitantes de ciclosporina ou oclacitinib para aliviar seus sinais clínicos. Ambas as drogas podem afetar a indução de tolerância adequada ao inibir a indução de células T reguladoras (Treg). Hipótese/Objetivos: Avaliamos o número de células Treg e os níveis séricos de interleucina (IL)‐10 e fator transformador de crescimento beta (TGF‐β)1 em cães diagnosticados com dermatite atópica (DA) e tratados com sucesso com ciclosporina ou oclacitinib por nove ou mais meses. Animais: Foram incluídos 15 cães recebendo oclacitinib, 14 cães tratados com ciclosporina, 15 cães saudáveis, 13 cães com DA moderada a grave não tratada e 15 cães atópicos controlados com AIT. Materiais e Métodos: As porcentagens de células T CD4+CD25+FOXP3+ do sangue periférico foram determinadas por citometria de fluxo. As concentrações séricas de IL‐10 e TGF‐β1 foram medidas por ensaio imunoenzimático. Resultados: A porcentagem de células Treg no grupo ciclosporina foi significativamente menor em comparação ao grupo saudável ( p = 0, 0003), ao grupo DA não tratado ( p = 0, 0056) ou ao grupo AIT (p = 0, 0186). Não houve diferença significativa nas porcentagens de células Treg entre o grupo ciclosporina e oclacitinib, nem o oclacitinib e os cães saudáveis, ou oclacitinib e os cães com DA não tratados ou tratados com AIT. Não foram detectadas diferenças significativas nas concentrações séricas de IL‐10 e TGF‐β1 entre os cinco grupos. Conclusões e relevância clínica: Percentagens mais baixas de células Treg nos cães tratados com ciclosporina sugerem um impacto deste fármaco nesta população de células; no entanto, isso não significa necessariamente que diminui a tolerância. A funcionalidade e a produção de citocinas podem ser mais importantes do que o número de células Treg. Mais estudos avaliando o resultado do tratamento de cães recebendo AIT e drogas concomitantes são necessários para mostrar a relevância clínica.